2020
DOI: 10.1016/j.drugalcdep.2020.108221
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and opioid use disorder pharmacotherapy: A secondary analysis of a clinical trial

Abstract: Objective: To examine the health-related quality-of-life (HRQoL) of persons with opioid use disorder (OUD) seeking treatment in an inpatient detoxification or short-term residential setting; continuing treatment as outpatients. Methods:We conducted a secondary analysis of data from a clinical trial (N=508) where participants were randomized to extended-release naltrexone or buprenorphine-naloxone for the prevention of opioid relapse. We used a generalized structural equation regression mixture model to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Although our study demonstrated a relationship between decrease in QoL and relapse, it is unclear whether relapse preceded or followed a drop in rated QoL. This study supports the body of evidence that shows an association between QoL and relapse [ 42 , 43 , 44 ], however, causation has not been established. One study examining QoL and alcohol use disorder found that improved QoL was associated with abstinence at six months, yet it could not determine if it operated as a predictor [ 42 ].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although our study demonstrated a relationship between decrease in QoL and relapse, it is unclear whether relapse preceded or followed a drop in rated QoL. This study supports the body of evidence that shows an association between QoL and relapse [ 42 , 43 , 44 ], however, causation has not been established. One study examining QoL and alcohol use disorder found that improved QoL was associated with abstinence at six months, yet it could not determine if it operated as a predictor [ 42 ].…”
Section: Discussionsupporting
confidence: 71%
“…Researchers examining the role of QoL satisfaction in recovery found overall satisfaction was associated with sustained abstinence, and in fact predicted remission at 1 year [ 43 ]. Another found that MOUD initiation and maintenance is imperative to improved QoL and sustained abstinence [ 44 ]. Intriguingly, a subgroup in this study who reported higher levels of substance use, legal and psychiatric problems, and inadequate family and social support did not show an improvement in quality of life related to MOUD, but instead with social support services.…”
Section: Discussionmentioning
confidence: 99%
“…The ASI composite score variables were continuous and ranged from 0 to 1. An increase in the ASI composite score indicates increased severity in the associated construct and have been shown to be associated with HRQoL in prior studies [ 38 42 ]. The time-varying ASI composite scores were advantageous to the research objective of evaluating determinants of HRQoL surrounding release from incarceration, given the theoretical importance of the information contained therein, and their proximity to the outcomes of interest.…”
Section: Methodsmentioning
confidence: 99%
“…Quality of life as a classification of OUD care quality measurement is imperative because it both predicts treatment retention and is a clinical endpoint itself. [69][70][71][72] While quality of life measurement for OUD remains underdeveloped and is rarely incorporated into practice, it has nevertheless garnered attention over the last decade as part of healthcarewide trends toward value-based payment. OUD's immense societal cost is predominantly attributable to decreased quality of life.…”
Section: Quality Of Lifementioning
confidence: 99%